The Difference between Moderate and Limited Communitarianism - Lungelo Siphosethu MBATHA (Arụmarụka)
This article uses philosophical analysis to defend the status of limited communitarianism as a standalone theory in African political philosophy. Early African scholars like Ifeanyi Menkiti argued that the community takes priority over the individual in all important respects. However, these thinkers were soon labelled radical or extreme in their treatment of the individual and were requested to moderate or restrict their articulation of the community’s role. This gave birth to the radical and moderate theories. But not before long, the moderates were also accused of supporting the tyranny of the community. They were also accused of not being fundamentally different from the radicals, giving rise to the limited version of Afro-communitarianism. Yet, the status of this latest instalment as a standalone theory has been doubted, with critics claiming that the limited version is not different to, or is merely another well-argued variant of, moderate communitarianism. This article argues that upon critical philosophical analysis, there is good reason to conclude that Bernard Matolino’s limited communitarianism is different from (and not just a well-argued version of) Kwame Gyekye’s moderate communitarianism. The paper argues that while there are similarities between the theories, the differences which exist in the definitions of persons and community and how the relationship between the two is understood in terms of rights, duties, and primacy make moderate and limited communitarianism distinct standalone theories.